ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN BUSANA MUSLIM DENGAN MENGGUNAKAN METODE REGRESI LOGISTIK BINER: STUDI KASUS : BUTIK NAUFAL BALARAJA KABUPATEN TANGERANG - R. Aditama; Linah Marlinah (Prodi Matematika FMIPA Unirow Tuban, 2022)
This study discusses the analysis of factors regarding the decision to purchase Muslim clothing (case study of Naufal Boutique, Balaraja District). The sample in this study amounted to 93 respondents. The method used in this study is a binary logistic regression method with the G test, Wald's test. With the product quality variable (X1) having a positive and significant effect of 85.5% and the price variable (X2) positive and significant effect of 26.4%. Keywords – Price, Quality, Purchase Decision, Logistic Regression